2011
DOI: 10.3109/0886022x.2011.560408
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Alfacalcidol Once Weekly Pulse Therapy for Secondary Hyperparathyroidism in Hemodialysis Patients

Abstract: Background: This study was carried out to assess the efficacy of intravenous administration of alfacalcidol once weekly versus thrice weekly in patients with poorly controlled secondary hyperparathyroidism. Methods: Thirty-six hemodialysis patients with intact parathyroid hormone (i-PTH) > 31.8 pmol/L were divided into two groups. Eighteen patients (Group 1) were given once weekly alfacalcidol for 6 months. The starting dose was 3 μg, which was increased or decreased by 1 μg per week. Eighteen patients (Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several studies have shown that alfacalcidol is effective for SHPT control when compared to others forms of activated vitamin D [19-22]. Mitwalli et al [14] reported in 2000 that oral intermittent administration of alfacalcidol was at least as effective as IV administration in controlling serum PTH.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that alfacalcidol is effective for SHPT control when compared to others forms of activated vitamin D [19-22]. Mitwalli et al [14] reported in 2000 that oral intermittent administration of alfacalcidol was at least as effective as IV administration in controlling serum PTH.…”
Section: Discussionmentioning
confidence: 99%